PENGEMBANGAN MODUL DIGITAL MATERI TEKS CERITA NARASI PADA SISWA KELAS VII SMP - Riska Harahap; Hermanto Hermanto; Riswanda Himawan (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2022)
The background of the research was due to the COVID-19 pandemic which was not over yet and the need for teaching materials that could be used digitally. This is of course based on the results of a need assessment or analysis of product needs in the two schools that are partners in this research. The product that appears in this study is a digital module that contains narrative text material for seventh grade students of junior high school. The purpose of this research is to find out; 1) the stages in developing a digital module for narrative text material for seventh grade junior high school students, 2) the feasibility of developing a digital module for narrative text material for seventh grade junior high school students, 3) implementing digital module development for seventh grade junior high school students. The type of research used in this research is research and development with the ADDIE development model (Analysis, Design, Development, Implementation and Evaluation). The research subjects are validators in the form of media experts, material experts, learning experts (users), and students. While the object of this research is the development of a digital module containing narrative text material for seventh grade students of junior high school. Data collection techniques used in this study were observation, interviews, and questionnaires. Meanwhile, the data analysis technique used in this study uses quantitative-descriptive analysis, because it presents data from the validation results in the form of numbers and describes the stages in product development in the form of digital modules. The results of this study are as follows, showing that the teaching materials that have been developed can be categorized as "Very Appropriate". This is evidenced by the results of the average score obtained from the experts, amounting to 97.6. The average score obtained from media experts is 106, from material experts is 96, and from teaching experts (teachers as users) is 92. The results of student responses to digital modules that have been implemented are 95.5. Based on this explanation, it can be concluded that research on the development of digital modules for narrative text material for seventh grade students of junior high school is expected to be able to use this digital module optimally in the process of teaching and learning activities and of course it can improve the quality of the process and learning outcomes in narrative texts.